Pengaruh Promosi terhadap Volume Penjualan Gula Aren Tropica Sidimco - Irmala Fitri Siregar (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2018)
The purpose of this study was to determine the effect of promotion on increasing sales of Sidimco Tropica palm sugar. This research was conducted in the household industry of Sidimco Tropica palm sugar processing in Kelutahan Losung Batu, Padangsidimpuan Hutaimbaru District, Padangsidimpuan City. It is starting from April to June 2016. The population in this study are all buyers of Sidimco tropical palm sugar. The sampling technique is done by accidental sampling method which is a sampling technique based on coincidence, i.e., anyone who happens to meet with researchers can be used as a sample if it is deemed that the person met by chance is suitable as a source of data totaling 40 people. The analytical method used is a Simple Regression Analysis to estimate to obtain the functional relationship of the independent variable (Promotion) to the dependent variable (Increase in Sales). The results showed that based on the statistical test results obtained a significant value / probability = 0.03 or smaller than the value